What is in a name? (some personal thoughts) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Name changing goes hand in hand with new governments; this has happened all over the world. Name changing has become part of South Africa in recent times and seems to l continue in the near future. Name changing confuses the man on the street, teachers and learners. Text books and atlases become outdated and this involves costs. Most names represent the history, people and topography of the area.
Keywords: Name changing; new governments